Clinical Features of Cytomegalovirus Retinitis in HIV Infected Patients - Tang, Yang; Sun, Jianjun; He, Taiwen; Shen, Yinzhong; Liu, Li; Steinhart, Corklin R.; Chen, Jun; Qi, Tangkai; Wang, Zhenyan; Song, Wei; Zhang, Renfang (Frontiers in Cellular and Infection Microbiology, 2020)
Objectives: The purpose of this study was to investigate the clinical features and related laboratory indicators of cytomegalovirus retinitis in HIV infected patients in order to find a suitable laboratory reference guide to aid in the early diagnosis of CMVR, which should improve the prognosis of the severe retinitis. Methods: PLHIVs who were admitted to our hospital from January 2010 to December 2016 were included. The diagnosis of AIDS follows the AIDS Treatment Guidelines. Levels of CMV IgG and IgM were measured by ELISA in order to detect the CMV infection status of the patient. CMV-DNA levels were assessed by a quantitative PCR method, and CD4+ T lymphocytes were detected by flow cytometry. Logistical regression was used to analyze the risk factors for CMV retinitis in HIV-infected patients.. Results：There were 93 patients with HIV that were also diagnosed with CMV retinitis. After ART, the intraocular pressure, visual acuity, cotton plaque incidence, and CD4+ T lymphocyte count were significantly improved, and the yellow-white retinal lesions gradually disappeared. In patients with HIV infections, the CD4+ T lymphocyte count, and peripheral blood quantitative CMV-DNA levels were found to be independent risk factors for CMV retinitis (P<0.05). Patients with HIV infection who had CMV-DNA levels >6390 copies/mL were associated with more severe ophthalmolgic conditions related to CMV retinitis. Conclusion：Patients with HIV infections with quantitative CMV-DNA levels > 6390 copies/mL have a higher probability of having a diagnosis of CMV retinitis and a worse prognosis than those whose CMV-DNA level is less than 6390 copies/mL.